Probability distribution characteristics of summer extreme precipitation in Xinjiang, China during 1970–2021 - Ailiyaer Aihaiti; Yu Wang; Mamtimin Ali; Lianhua Zhu; Junjian Liu; Hailiang Zhang; Jiacheng Gao; Cong Wen; Meiqi Song (Theoretical and Applied Climatology, 2023)
Based on the daily precipitation data of 96 stations in Xinjiang, China, from 1970 to 2021, the trend of summer extreme precipitation indices and their regional characteristics are analyzed. The generalized extreme value (GEV) model is used to investigate the probability distribution characteristics of summer extreme precipitation indices in northern, southern, and eastern Xinjiang. The results show that (1) The summer maximum 1-day precipitation (RX1day) and maximum 5-day precipitation (RX5day) of most stations in Xinjiang showed an increasing trend, while the summer consecutive dry days (CDD) showed a decreasing trend. (2) The climatology (mean intensity) of RX1day, RX5day, and CDD at most stations in northern Xinjiang were more than 10 mm, more than 15 mm, and less than 25 days, respectively, while those at most stations in southern and eastern Xinjiang were less than 10 mm, less than 15 mm, and more than 25 days. The regional averaged climatology and inter-annual variability of RX1day/RX5day (CDD) in southern and eastern Xinjiang were smaller (larger) than that in northern Xinjiang. (3) The 20-year return level (RL20) of RX1day, RX5day, and CDD at stations in northern Xinjiang were 19.38–56.57 mm, 28.05–70.91 mm, and 22.51–51.05 days, respectively. The RL20 of RX1day, RX5day, and CDD at stations in southern Xinjiang were 21.31–46.07 mm, 23.99–72.89 mm, and 14.94–89.80 days, respectively. The RL20 of RX1day, RX5day, and CDD at stations in eastern Xinjiang were 8.89–36.36 mm, 10.13–50.66 mm, and 26.75–92.00 days, respectively. Compared with northern Xinjiang, there were lesser RX1day and RX5day events, with weaker intensity and smaller variability in southern and eastern Xinjiang. And the CDD events were opposite.